STUDENTS’ PERCEPTIONS TOWARD THE USE A SONG AS A MEDIA FOR SPEAKING SKILL AT SMA NEGERI 1 KOTAMOBAGU - Sistrodikromo, Monalisa; Tuna, Jim R.; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research has the purpose of analyzing the perception of the students towards the use of songs in learning speaking in English. This research was conducted in the form of quantitative which means that the result of this research is in the form of numbers. The data source of this research comes from questionnaires that were given to the students in SMA Negeri 1 Kotamobagu. The sample of this research comes from Class XI F which consist of 32 students. Furthermore, Likert Scale was used in finding out the students’ perception of using songs in learning speaking in English. The result of the study shown that, 87% of the total sample strongly agreed that the use of songs can improve students’ speaking skill. It can be concluded that song is considered effective to improve students’ speaking skill when used as a material in teaching English as a subject in SMA Negeri 1 Kotamobagu